PH‐Dependent Slipping and Exfoliation of Layered Covalent Organic Framework. Issue 57 (11th September 2020) - Ahmed, Saud Asif; Liao, Qiao‐Bo; Shen, Qi; Ashraf Baig, Mirza Muhammad Faran; Zhou, Juan; Shi, Cai‐Feng; Muhammad, Pir; Hanif, Sumaira; Xi, Kai; Xia, Xing‐Hua; Wang, Kang
Abstract: Layered/two‐dimensional covalent organic frameworks (2D COF) are crystalline porous materials composed of light elements linked by strong covalent bonds. Interlayer force is one of the main factors directing the formation of a stacked layer structure, which plays a vital role in the stability, crystallinity, and porosity of layered COFs. The as‐developed new way to modulate the interlayer force of imine‐linked 2D TAPB‐PDA‐COF (TAPB = 1, 3, 5‐tris(4‐aminophenyl)benzene, PDA = terephthaldehyde) by only adjusting the pH of the solution. At alkaline and neutral pH, the pore size of the COF decreases from 34 Å due to the turbostratic effect. Under highly acidic conditions (pH 1), TAPB‐PDA‐COF shows a faster and stronger turbostratic effect, thus causing the 2D structure to exfoliate. This yields bulk quantities of an exfoliated few/single‐layer 2D COF, which was well dispersed and displayed a clear Tyndall effect (TE). Furthermore, nanopipette‐based electrochemical testing also confirms the slipping of layers with increase towards acidic pH. A model of pH‐dependent layer slipping of TAPB‐PDA‐COF was proposed. This controllable pH‐dependent change in the layer structure may open a new door for potential applications in controlled gas adsorption/desorption and drug loading/releasing. Abstract : Exfoliation : Slipping of layers and exfoliation of a TAPB‐PDA‐COF (TAPB = 1, 3, 5‐tris(4‐aminophenyl)benzene, PDA = terephthaldehyde, COF=covalent organic framework) with a decrease of the pH value in solution was investigated. The controllable pH‐dependent change in the layer structure may be useful for applications in drug release or gas adsorption/desorption.